2017
DOI: 10.5586/asbp.3543
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the distribution of rare and interesting moss species of the family Orthotrichaceae (Bryophyta) in Tajikistan and Kyrgyzstan

Abstract: Bryological research carried out from 2008 in Tajikistan and Kyrgyzstan brought interesting data on the occurrence of epiphytic bryophytes which have not been recorded yet there. One of the species was recently described as a new (Orthotrichum pamiricum) and some of the other newly recorded species are considered as rare or endangered in the region of Middle Asia. To make detailed field monitoring of the species with the aim of mapping their distribution in a wild and complex mountainous terrain, it was necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Due to the fact that detailed research of epiphytic bryophytes was performed only on the area of tea plantations, we do not have relevant data available for comparison with the species diversity of bryophytes growing in other communities in the area. However, the observations in other regions show that the diversity of mosses growing epiphytically on old solitary trees, terrestrially on open soil or on the surface of stones along plantations is significantly lower 6,19,108 . This is mainly due to influence of the microclimatic conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the fact that detailed research of epiphytic bryophytes was performed only on the area of tea plantations, we do not have relevant data available for comparison with the species diversity of bryophytes growing in other communities in the area. However, the observations in other regions show that the diversity of mosses growing epiphytically on old solitary trees, terrestrially on open soil or on the surface of stones along plantations is significantly lower 6,19,108 . This is mainly due to influence of the microclimatic conditions.…”
Section: Discussionmentioning
confidence: 97%
“…The growth of these cushions is more closely associated with temperature than with precipitation. A previous species distribution modeling study also found that higher values of annual temperature range over the year led to a lower habitat suitability for bryophytes of Orthotricaceae [44]. A temperature increase in the tropics could be more severe than the change in precipitation and could subsequently impact the distribution of tropical bryophytes.…”
Section: Temperature and L Aduncum Distributionmentioning
confidence: 87%
“…According to Wierzcholska et al [ 10 ], loss of mature forest ecosystems is a more important threat to woodland-specialist epiphytic bryophytes than climate change, which results from limited dispersal capabilities and specific habitat requirements. However, habitat fragmentation seems to have more disastrous effects on moisture-loving species, than on drought-resistant ones [ 13 , 77 ]. Thus, we can assume that representatives of the Orthotrichaceae family connected with dryer ecoregions (e.g., Lewinskya affinis , L. hookeri , L. speciosa , L. vladikavkana , Nyholmiella obtusifolia , Orthotrichum alpestre , O. anomalum , O. callistomum , O. crenulatum , O. dasymitrium , O. pallens , O. pamiricum , O. scanicum , O. sordidum , O. urnigerum , and Ulota robusta ) will be more resistant to future climate warming than those from humid ones (e.g., Leratia exigua , Macromitrium gymnostomum , M. cavaleriei , O. consobrinum , O. crispifolium , O. griffithii , and Ulota gymnostoma ).…”
Section: Discussionmentioning
confidence: 99%